Host microbiome in tuberculosis: disease, treatment, and immunity perspectives - Pant, Archana; Das, Bhabatosh; Arimbasseri, Gopalakrishnan Aneeshkumar (Frontiers in Microbiology, 2023)
Tuberculosis (TB), an airborne pulmonary disease caused by Mycobacterium tuberculosis (M. tb), poses an unprecedented health and economic burden to most of the developing countries. Treatment of TB requires prolonged use of a cocktail of antibiotics, which often manifest several side effects, including stomach upsets, nausea and loss of appetite spurring on treatment non-compliance and the emergence of antibiotic resistant M. tb. The anti-TB treatment regimen causes imbalances in the composition of autochthonous microbiota associated with the human body, which also contributes in major side effects. The microbiota residing in the gastrointestinal tract play important role in various physiological processes, including resistance against colonization by pathogens, boosting host immunity, and providing key metabolic functions. In TB patients, due to prolonged exposure to antituberculosis drugs, the gut microbiota significantly loses its diversity and several keystone bacterial taxa. This loss may result in a significant reduction in the functional potency of the microbiota, which is a probable reason for poor treatment outcomes. In this review, we discuss the structural and functional changes of the gut microbiota during TB and its treatment. A major focus of the review is oriented to the gut microbial association with micronutrient profiles and immune cell dynamics during TB infection. Furthermore, we summarize the acquisition of antimicrobial resistance in M. tb along with the microbiome-based therapeutics to cure the infections. Understanding the relationship between these components and host susceptibility to TB disease is important to finding potential targets that may be used in TB prevention, progression, and cure.